Hydrologic Connectivity of Head Waters and Floodplains in a Semi‐Arid Watershed. (December 2013) - Ochoa, Carlos G.; Guldan, Steven J.; Cibils, Andres F.; Lopez, Stephanie C.; Boykin, Kenneth G.; Tidwell, Vincent C.; Fernald, Alexander G.
Abstract Hydrologic connectivity can be important when assessing the role of water availability and distribution in sustaining different natural processes and human activities in a given landscape. We present a study that served as one of five case studies for an interdisciplinary modeling course. The main objectives of the study presented are: 1) to characterize the hydrologic connectivity between the uplands and the irrigated valley and; 2) to set the foundations for understanding the connections between hydrology and complementary disciplines of ecology, rangeland management, and system dynamics modeling in a semiarid watershed in the southwestern United States. Study results show a strong hydrologic connectivity between surface and groundwater in the lower agricultural valley that follows a seasonal pattern, driven primarily by irrigation contributions to the shallow aquifer. The interdisciplinary modeling team assigned to this study was able to use data from it and outside sources to create a working model that addressed these interconnections and highlighted the study value of concurrent consideration of multiple components of linked hydrologic, economic, ecological, and social systems.